Flooding Distributed Denial of Service Attacks-A Review - Wan Mohd Ghazali, Khadijah; Hassan, Rosilah (Science Publications, 2011)
Flaws either in users’ implementation of a network or in the standard specification of protocols has resulted in gaps that allow various kinds of network attack to be launched. Of the kinds of network attacks, denial-of-service flood attacks have caused the most severe impact. Approach: This study reviews recent researches on flood attacks and their mitigation, classifying such attacks as either high-rate flood or low-rate flood. Finally, the attacks are compared against criteria related to their characteristics, methods and impacts. Results: Denial-of-service flood attacks vary in their rates, traffic, targets, goals and impacts. However, they have general similarities that are the methods used are flooding and the main purpose is to achieve denial of service to the target. Conclusion/Recommendations: Mitigation of the denial-of-service flood attacks must correspond to the attack rates, traffic, targets, goals and impacts in order to achieve effective solution.